Navigating the Thesis Journey: Challenges Faced by Graduate Students in Liberian Universities - Forkpah, Eric; Karpee Saybay, James (Wangsa : Journal of Education and Learning, 2024)
This investigation examined the difficulties encountered by graduate students at Liberian universities during the thesis writing process. It emphasized various barriers: academic, financial, and support-related challenges. For instance, limited access to research resources posed significant hurdles, however financial constraints and a lack of adequate mentorship—due to a high faculty-to-student ratio—also played crucial roles. Although the study delved into strategies for overcoming these obstacles, such as time management techniques and online collaborative tools, it revealed that many students struggled to implement these methods effectively. Utilizing a mixed-methods approach which combined quantitative surveys and qualitative interviews, the research offered a thorough understanding of these impediments. Furthermore, it proposed actionable recommendations—like improved access to libraries and digital resources, enhanced mentorship programs, and workshops focused on time management and research skills—to bolster thesis support systems thus promoting overall academic success for graduate students in Liberia.